Boundary Layer Impedance model to analyse the visco-thermal acousto-elastic interactions in centrifugal compressors. (August 2018) - Jith, Jithin; Sarkar, Sunetra
Abstract: Conventional acousto-elastic interaction studies on centrifugal compressors generally ignore the dissipative effects of visco-thermal phenomena present in all acoustic fluids. This work presents a numerically efficient framework for solving acousto-elastic problems, while taking visco-thermal effects into consideration, in centrifugal compressor-like geometries in the frequency domain. Compared to conventional acousto-elastic analyses, the framework enables the computation of a more realistic estimate of the frequency response of a centrifugal compressor. The acoustic fluid is modelled using Boundary Layer Impedance (BLI) model which accounts for dissipative visco-thermal effects through an impedance-like boundary condition. An improved finite element implementation is presented which reduces the computational time of the BLI acousto-elastic model to almost half, while not compromising on accuracy. To further reduce the computational cost, a Krylov subspace based reduced order model (ROM) is developed and implemented in the analysis. The ROM is specifically designed to handle frequency dependent system matrices encountered in the BLI acousto-elastic analysis. Highlights: A numerically efficient visco-thermal acousto-elastic framework is proposed. Fluid is modelled using a one-step (more efficient) Boundary Layer Impedance model. Model order reduction is performed using a frequency dependent rational Krylov method. Damping ratios are seen to decrease as pressure in the side-cavities increases.